PENGGUNAAN MEDIA VISUAL DALAM PEMBELAJARAN PAI - Nurotun Mumtahanah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
In the current era of globalization, inevitably that there have been many types and forms of learning media ranging from the simple to high-tech ones. The more complete media is used, the better the results are achieved. All educators and teachers are expected to choose the media that is good and is in accordance with the condition of students and subject matters in order to achieve the learning objectives, because the ability of teachers to choose the medium of education will determine the quality of teaching and learning processes. The use of instructional media in the learning process can also generate new desires and interests to encourage motivation and stimulation of learning activities and even bring a psychological impact on students. The use of instructional media at the stage of learning orientation will greatly help the effectiveness of the learning process and the delivery of messages and learning contents. Understandably that media is inseparable part of the learning process because it can arouse students' learning achievement and learning activities and expedite / help meet the learning objectives. One of the various learning media is the use of visual media.